Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan

Tryptophan environment and functional characterization of a kinetically stable serine protease containing a polyproline II fold - Rohamare, Sonali B.; Gaikwad, Sushama M. (Journal of Fluorescence, 2014)
The single tryptophan residue from Nocardiopsis sp. serine protease (NprotI) was studied for its microenvironment using steady state and time-resolved fluorescence. The emission maximum was observed at 353 nm with excitation at 295 nm indicating tryptophan to be solvent exposed. Upon denaturation with 6 M guanidinum thiocyanate (GuSCN) the emission maxima was shifted to 360 nm. Solute quenching studies were performed with neutral (acrylamide) and ionic (I- and Cs+) quenchers to probe the exposure and accessibility of tryptophan residue of the protein. Maximum quenching was observed with acrylamide. In the native state, quenching was not observed with Cs+ indicating presence of only positively charged environment surrounding tryptophan. However; in denatured protein, quenching was observed with Cs+, indicating charge reorientation after denaturation. No quenching was observed with Cs+ even at pH 1.0 or 10.0; while at acidic pH, a higher rate of quenching was observed with KI. This indicated presence of more positive charge surrounding tryptophan at acidic pH. In time resolved fluorescence measurements, the fluorescence decay curves could be best fitted to monoexponential pattern with lifetimes of 5.13 ns for NprotI indicating one conformer of the trp. Chemical modification studies with phenyl glyoxal suggested presence of Arg near the active site of the enzyme. No inhibition was seen with soyabean trypsin and limabean inhibitors, while, CanPI uncompetitively inhibited NprotI. Various salts from Hofmeister series were shown to decrease the activity and PPII content of NprotI.
Keywords: Fluorescence quenching; Hofmeister series; Nocardiopsis; Serine protease; Tryptophan

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding